Pengaruh Karakteristik Industri, Negara, dan Faktor Makroekonomi terhadap Tingkat Utang - Cynthia Afriani Utama; Ahja Haziqo (The Indonesian Journal of Accounting Research, 2013)
The study investigates whether the level of financial leverage is affected by industry type (i.e. lodging or software industries), macroeconomic factors (measured by inflation rate and GDP per capita), and country characteristics. Generally, lodging firms are characterized by higher asset tangibility than software firms. Consequently, higher growth opportunities do not prevent  the firms to use more debt because asset tangibility can be used as a collateral of debt. The sample includes listed firms in the lodging and software industries and are from Indonesia, Malaysia, and Singapore. As previous studies, this study finds that growth opportunities negatively affect the level of financial leverage, but this negative effect weakens as the use of fixed assets (i.e., asset tangibility) increases. In addition, lodging firms have more leverage than the software firms. Further, the study finds that higher GDP per capita and lower inflation rate translate to lower use of debt.